Learning Anatomy with Augmented Reality: learning design and app design for optimal learning - Nørgård, Cita; O’Neill, Lotte Dyhrberg; Chemnitz, John; Majgaard, Gunver (Tidsskriftet Læring og Medier (LOM), 2019)
An Augmented Reality (AR) application was developed to help students at SDU to learn the anatomy of the human body (mediastinum). This research project intended to evaluate whether AR strengthened the students’ self-efficacy and motivation, improved learning, and provided a good learning experience. This study focusses on how AR can help students to translate two-dimensional into three-dimensional understanding and evaluates formats of the app (the use of quizzes) together with the didactic design of the teaching sessions with AR. The objectives were to examine A. the effectiveness of using AR on student’s short, long term, and transfer learning outcome compared with traditional teaching, B. the effect of quizzes, and C. app design in relation to didactic design. In the AR world students saw a standardized hologram body combined with selected images from a computed tomography (CT) scan. The CT images were presented at the proper spatial positions in a hologram body. The user could select which structures to be shown at the body (e.g. skin, the vascular system, etc.). They could approach the body, circumvent it, study structures in details and compare the concurrent presentation with the different CT images. During class one group received traditional teaching and two groups studied CT scans in Augmented Reality. One AR-group complemented the AR app with quiz questions and received corrective feedback. The other AR group did not use quiz questions but studied content on their own hand. A teacher was present and ready to help students in all groups. The aim of this paper is to share lessons learned from this intervention and suggest solutions for app design and learning design to facilitate deeper learning processes and scaffold learners’ needs with AR as a learning resource.